Defying Expectations: Gender Roles and the Balance of Masculine and Feminine Traits in Disney’s Mulan (2020) - Vanessa; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study analyses Disney’s live-action Mulan (2020), focusing on Mulan’s defiance of traditional roles. This movie highlights the theme of female empowerment as she frees herself from conventional female roles. This study examines Mulan’s behaviors that are inconsistent with the expected gender roles, leading to her liberation by embracing both her feminine and masculine traits. This analysis employs two main theories: The social Role theory, which focuses on gender roles, and Confucianism as a supporting concept, to analyze Mulan’s behaviors that are inconsistent with traditional roles. The second one is the Bem Sex Inventory, which identifies the masculine and feminine traits that Mulan embodies, incorporating Giddens’ concept of agency to analyze the ways Mulan liberates herself from the expected roles. The finding reveals that Mulan’s defiance comes from her desire to remain true to herself as she liberates herself by embracing her feminine and masculine traits.